Full-length cDNA cloning and protein three-dimensional structure modeling of factor VII of rhesus monkey, Macaca mulatta - Wang, J.; Tan, W.; Chen, Younan; Lu, X.; Lu, Y.; Qin, S.; Li, S.; Bu, H.; Li, Y.; Cheng, J. (2008)
FVII is a vitamin K dependent serine protease that plays a key role in extrinsic coagulation pathway. In this paper, we report the full-length cDNA sequences of rhesus monkey FVII. The full-length cDNA has 2424 bp, and predicts an open reading frame of 1416 bp corresponding to 472 amino acids. The deduced protein sequence of rhesus monkey FVII indicates the functional domains including signal peptide, Gla domain, two EGF domains, and catalytic domain. Rhesus monkey FVII is highly homologous to human FVII with amino acid identity of 91.0%. Comparison of three-dimensional protein structure shows high conservation between them. The important functional sites such as the N-terminal ?-carboxyglutamic acids of the Gla domain, the Ca2+ binding region of the EGF I domain, the TF binding region, the active site binding cleft, and the macromolecular substrate binding exosite of trypsin domain are all well conserved in FVII of rhesus monkey. Prothrombin time test shows rhesus monkey FVII has a similar clotting time with that of human. This study of rhesus monkey FVII might be helpful for understanding the function compatibility of human and rhesus monkey FVII, which is beneficial for the study of xenotransplantation. © 2007 Elsevier Inc. All rights reserved.